Variáveis evidenciadoras dos processos de transformação do campo : O caso do Espírito Santo - Brasil - Ferraz do Nascimento, Patrícia (Mundo Agrario.)
This article aims to analyze the occurrence of changes in the countryside, in Brazil, from the observation of variables such as type of job, income, family profile, access to consumer goods, services, and information and communication technology. There had been used exploratory analysis and logistic regression method, based on data from the Pesquisa Nacional de Amostra de Domicílios (Brazilian National Household Sample Survey - PNAD) for the state of Espirito Santo. The study found that about 27.2of individuals who had lived in the countryside report an urban profile, revealing that the urban lifestyle is encompassed not only in the city